Life on the edge: mineral incrustations colonized by fungal communities in the sulfur fumarole on Sierra Negra volcano (Galápagos Archipelago) - Maria Landolfi; Raphael Tiziani; Sahra Riviere; Fabio Trevisan; Mariagioia Petraretti; Heinke Jäger; Stefano Cesco; Martin H. Gerzabek; Katharina Keiblinger; Franz Zehetner; Federica Villa; Tanja Mimmo; et al. (Royal Society Open Science)
Despite the extensive studies on plant and animal endemism in the Galápagos Islands, fungal diversity remains largely unexplored, particularly in fumarole environments. Here, we explore the fungal diversity in two gypsum incrustations within an active fumarole of Sierra Negra volcano (Isabela Island). We hypothesize that minor differences in the chemical and mineralogical characteristics of these substrates, despite similar environmental conditions, lead to distinct fungal communities with substrate-specialized taxa. Alpha diversity indices showed no significant differences, but beta diversity analysis revealed two distinct fungal communities (PERMANOVA p < 0.01), with only 3.31% of operational taxonomic units (OTUs) shared between incrustations and 37.75 and 14.57% uniquely associated with each incrustation. A strong correlation was found between beta diversity and most measured chemical parameters (Mg, S, Fe, Na, Al, Mn, Zn, K, P, Cu). Our findings indicate that even minor differences in the mineral and chemical composition of closely located incrustations significantly influence fungal communities, emphasizing these deterministic factors as key drivers in shaping fungal diversity.